THE EFFECTIVENESS OF TEACHING WRITING IN PROCEDURE TEXT BY USING MIND MAPPING STRATEGY AT THE FIRST GRADE STUDENTS OF MTs MIFTAKHUL FALAAH KEDIRI - Elfidah, Dhorifatun Niswa (LENTERA : Jurnal Pendidikan dan Pengajaran; Vol 9 No 3 (2019): LENTERA : Jurnal Pendidikan dan Pengajaran, 2019)
The aim of this research is to describe the effectiveness of teaching writing in procedure text by using mind mapping strategy at the first grade students of MTs. Miftakkhul Falaah Kediri in academic year 2014/2015. The research design which was used in this research was quantitative experimental with one group of pre-test and post-test design. The subjects of this research were the First Grade students of A class. The instruments which were used in this research were pre-test and post-test where pre-test was given before doing treatments and post-test was given after doing treatments to the students in experimental class. The data gotten were statistically computed by SPSS 15.0 version. The result of this research showed that t-test was 15,70 and significant  (2 tailed). It was higher than t.table at either 5% or 1% significant level. It meant that there is significant difference of studentsâ€™ writing ability in procedure text before and after being taught by using mind mapping strategy. So it could be concluded that teaching writing in procedure text by using mind mapping strategy at the first grade students of MTs. Miftakhul Falaah Kediri is effective.